Persepsi Wisatawan Terhadap Museum Bali Sebagai Daya Tarik Wisata Budaya - Wirayanthi, Ni Luh Yuning; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2018)
The museum is one of the cultural heritages that should be preserved. Museum Bali is one of the old museum is located in the city of Denpasar and became an icon of cultural tourism. The purpose of this study to determine the perceptions and motivations of tourists to Museum Bali as cultural tourist attractions in Denpasar. This study uses primary data and secondary. Data collection technique used observation, interview, questionnaire, and documentation. Sampling technique using the formula slovin by sampling using accidental sampling devoted to 96 respondents. To analyze data using qualitative descriptive. The results of this study indicate that the perception of tourists to Museum Bali shows a good response because from 17 indicators used as a measure of the response has been positive, there are two indicators  got  bad response. Advice can be given is the need for more interesting information and support so that tourists are more interested to know the collections of the Museum Bali. There needs to be a cultural attraction, the better promotion and attractive to increase the number of tourist visits.   Keywords : Tourist Perception, Museum, Cultural Tourist Attraction